Influence of Malnutrition on Adverse Outcome in Children with Confirmed or Probable Viral Encephalitis: A Prospective Observational Study. (28th January 2015) - Singh, Priyanka; Bhatt, Girish C.; Singh, Vijay; Kushwaha, K. P.; Mittal, Mahima; Mehta, Anita; Sharma, Bhoopendra; Pakhare, Abhijit P.; Kumar, Abhishek
Abstract : A prospective observational study was conducted in a tertiary care teaching hospital from August 2008 to August 2009 to explore the independent predictors of adverse outcome in the patients with confirmed/probable viral encephalitis. The primary outcome variable was the incidence of adverse outcomes defined as death or severe neurological deficit such as loss of speech, motor deficits, behavioural problems, blindness, and cognitive impairment. Patients with confirmed or probable viral encephalitis were classified into two groups based on their Z -score of weight-for-age as per WHO growth charts. Group I. Patients with confirmed or probable viral encephalitis with weight-for-age (W/A) Z -scores below −2SD were classified as undernourished. Group II. Patients with confirmed or probable viral encephalitis were classified as having normal nutritional status (weight-for-age Z -score >−2SD). A total of 114 patients were classified as confirmed or probable viral encephalitis based on detailed investigations. On multivariate logistic regression, undernutrition (adjusted OR: 5.05; 95% CI: 1.92 to 13.44) and requirement of ventilation (adjusted OR: 6.75; 95% CI: 3.63 to 77.34) were independent predictors of adverse outcomes in these patients. Thus, the results from our study highlight that the association between undernutrition and adverse outcome could be extended to the patients with confirmed/probable viral encephalitis.